Heat transfer in the mold during vertical continuous casting of steel - E. I. Marukovich; E. B. Demchenko (Литьë и металлургия)
The analysis of the performed researches has shown that the offered calculation technique is an effective means of management of formation process in casting. The found dependences and experimental data allow to calculate the specific value of the exactм heat flux in a given range of technological parameters obtained during a series of successful experiments for a particular casting method.Having the results of studies of the temperature regime of the mold during casting of a certain size and profile, it is possible to calculate the thermal state of the mold for the same casting process, but for the production of castings of any other size and profile.Having a certain amount of information on the temperature regime of the mold at different casting methods, you can use the solutions obtained to become the owner of a database containing the necessary information for solving the problems of solidification of the casting. In the subsequent design of equipment and equipment there is no need for additional experimental studies and analysis of the results.